Comparative genomics of Clostridium species associated with vacuum-packed meat spoilage. (May 2021) - Palevich, Nikola; Palevich, Faith P.; Maclean, Paul H.; Altermann, Eric; Gardner, Amanda; Burgess, Sara; Mills, John; Brightwell, Gale
Abstract: Bacterial species belonging to the genus Clostridium have been recognized as causative agents of blown pack spoilage (BPS) in vacuum packed meat products. Whole-genome sequencing of six New Zealand psychrotolerant clostridia isolates derived from three meat production animal types and their environments was performed to examine their roles in BPS. Comparative genome analyses have provided insight into the genomic diversity and physiology of these bacteria and divides clostridia into two separate species clusters. BPS-associated clostridia encode a large and diverse spectrum of degradative carbohydrate-active enzymes (CAZymes) that enable them to utilize the intramuscular carbohydrate stores and facilitate sporulation. In total, 516 glycoside hydrolases (GHs), 93 carbohydrate esterases (CEs), 21 polysaccharide lyases (PLs), 434 glycosyl transferases (GTs) and 211 carbohydrate-binding protein modules (CBM) with predicted activities involved in the breakdown and transport of carbohydrates were identified. Clostridia genomes have different patterns of CAZyme families and vary greatly in the number of genes within each CAZy category, suggesting some level of functional redundancy. These results suggest that BPS-associated clostridia occupy similar environmental niches but apply different carbohydrate metabolism strategies to be able to co-exist and cause meat spoilage. Highlights: Isolation of six psychrotolerant Clostridium strains associated with blown pack spoilage (BPS) in vacuum packed meat. Whole-genome sequencing revealed high levels of intra-species diversity. Comparative genomics showed a dual-clade structure containing two new putative Clostridium species. Isolates differ in their metabolic potential to utilise a variety of carbohydrate sources.